A VALIDATED LC-MS/MS METHOD FOR PHARMACOKINETIC STUDY OF CANAGLIFLOZIN IN HEALTHY RABBITS - Bhatt, Darshan; Rajkamal, B. (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: A liquid chromatography-tandem mass spectrophotometric (LC-MS/MS) method was developed for quantification of canagliflozin in rabbit plasma employing Liquid-Liquid extraction technique. Methods: Chromatographic separation was achieved on Inertsil ODS 5 µm C18, 50×4.60 mm with 30:70 v/v of 0.01M ammonium acetate: methanol as an isocratic mobile phase with a flow rate of 0.8 ml/min. The developed LC-MS method was applied to assess Cmax, t1/2, AUC0-t, and AUC0-inf of canagliflozin tablet after oral administration in healthy rabbits. Results: The developed method was linear over working range of 5ng/ml to 600ng/ml with a coefficient of correction (r2) = 0.999. The % recovery of the method was found to be 102.05%. The mean intraday and inter-day precision of the method was found to be 0.77 to 3.72%. The Canagliflozin showed Tmax of 1.58±0.2 and mean Cmax, AUC0®t andAUC0®a for Test formulation is 272±13.24, 2571.20±251and 2777.43±276 respectively. Conclusion: The developed method can be applied for routine analysis for quality control and the established LLOQ is sufficiently low to conduct a pharmacokinetic study with any marketing formulation of Canagliflozin in healthy rabbits.